Pengaruh Konformitas terhadap Perilaku Prososial Penumpang KRL Stasiun Bekasi pada Jam Sibuk - Putri Wulandari; Andreas Corsini Widya Nugraha; Arfian Arfian (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2026)
Passenger density on commuter trains during peak hours creates conditions that may influence individuals' social behavior. Although time pressure and crowded environments have the potential to reduce prosocial behavior, some passengers continue to demonstrate helping behaviors toward others. One factor that is assumed to contribute to the development of prosocial behavior is individuals' tendency to conform to the social norms prevailing in their surroundings. This study aimed to examine whether conformity influences the prosocial behavior of commuter train passengers at Bekasi Station during peak hours. A quantitative approach was employed using a simple linear regression design. The participants consisted of 113 commuter train passengers at Bekasi Station selected through purposive sampling. Data were collected using a conformity scale and a prosocial behavior scale and were subsequently analyzed using SPSS version 25. The regression analysis indicated that conformity had a positive and significant effect on prosocial behavior (F = 12.387; p = 0.001). The coefficient of determination (R² = 0.100) showed that conformity accounted for 10% of the variance in prosocial behavior. These findings suggest that higher levels of conformity to prevailing social norms are associated with a greater tendency to engage in prosocial behavior.